A trial speech screening test for school entrants. - Rigby, M J (1981)
An objective, low-cost means of screening school entrant children for speech disorders was designed, and speech therapists evaluated the doctor's screening results. In a field trial comprising 438 children, an accuracy rate of 92% was reported, with a referral rate by doctors of 14%, and speech therapists subsequently observing or treating 10%. The trial showed also the effects on accuracy rates of setting different pass levels.